Hesitant and anti-vaccination groups: A qualitative study on their perceptions and attitudes regarding vaccinations and their reluctance to participate in academic research- an example during a measles outbreak among a group of Jewish parents in Israel - Rana Hijazi; Anat Gesser-Edelsburg; Paula Feder-Bubis; Gustavo S. Mesch (Frontiers Media S.A., 2022)
BackgroundVaccination is widespread in Western countries and, overall, there is a high vaccination rate. However, immunization is still an enduring challenge. In recent years, the number of parents who choose to delay or refuse vaccines has risen.Objectives(1) to identify the perceptions and attitudes of hesitant and anti-vaccination parents regarding vaccination in general, and vaccinating their children in particular and; (2) to describe the responses of potential participants to the request to participate in academic research regarding their perceptions and attitudes on the subject of vaccines.MethodsThe research employs the qualitative hermeneutic phenomenological method using two research tools: (1) in-depth interviews with 7 hesitant and 11 anti-vaccination Jewish parents in Israel; and (2) the researchers' field notes from this study process, which describe the responses of 32 potential participants to the request to participate in this academic research.ResultsThe main findings indicate that while most of the interviewees admit to the efficacy of vaccines in preventing diseases, they oppose the way in which vaccines are promoted-based on providing partial information and disregarding parents' concerns and questions. Therefore, they demand transparency about the efficacy and safety of vaccines. The findings also point to a paradoxical finding. On the one hand, these groups claim that health organizations do not understand their position, referring to them as "science-deniers", even though they are not. On the other hand, these parents choose to refrain from participating in scientific studies and voicing their opinions, thereby perpetuating the situation of being misunderstood.ConclusionHesitant and anti-vaccination groups express mistrust in academic institutions and health organizations. Therefore, an effective dialogue that would include hesitant and anti-vaccination groups, the academy, and health organizations may contribute to a better understanding of the barriers that prevent these groups from getting vaccinated or vaccinating their children and promote public health.